The Effectiveness of Online Safety Awareness Campaigns in Reducing Risky Online Behavior Among University Students - Sinau, Macliffton Tembak (Journal of Law, Society and Policy Review, 2025)
The rapid expansion of digital technologies has increased university students' exposure to cyber risks, necessitating effective online safety awareness campaigns. This study examines the impact of such campaigns on reducing risky online behaviors among university students. Using a quantitative survey method, data was collected from students to assess their knowledge, engagement, and behavioral changes following participation in online safety programs. The findings indicate that targeted awareness campaigns significantly enhance students' understanding of cybersecurity risks, leading to a reduction in unsafe online activities, such as sharing personal information, engaging with phishing scams, and weak password management. The study highlights that frequent exposure to cybersecurity education fosters responsible digital behavior, reinforcing the importance of integrating online safety programs into university curricula. Additionally, the research underscores the need for adaptive and interactive training methods to sustain long-term behavioral change. This study contributes to the growing field of cybercrime prevention by providing insights into the effectiveness of digital safety education for young adults.